Inovasi Pancing Rawai dalam Kehidupan Nelayan Masyarakat Tondonggeu - Gevira, Dhea; Zainal, Zainal; Danial, Danial (JURNAL KABANTI: Kerabat Antropologi, 2025)
This study aims to identify and describe fishing gear innovations in Tondonggeu Village, Nambo Sub-district, Kendari City. The local fishing community faces various challenges such as declining cathes. Under these conditions, fishermen in Tondonggeu innovate fishing gear by modifying and developing traditional fishing gear to be more efficient, environmentally friendly, and in accordance with the characteristics of local waters. Some of the innovation include longline fishing rods, boats charts, and handline fishing rods. This study used a qualitative research method with an ethnographic approach. The technique of determining informants was done purposively. The data collection technique was carried out through involved observation (Particivation Observation), and in-depth interviews (In-depth Interview). The data collected was then analyzes using Everett M. Rogers’ Diffusion of Innovation Theory (1964). The result showed that the fishing gear innovation was able to increase fishermen’s catch and income and provide alternative solution during extreme weather seasons. Factors driving innovation include experience, economic need, environmental conditions, and limited available fishing gear. On the other hand, limited capital and lack of access to training are challenges to the sustainability of this innovation. This research is expected to be reference in the development of local wisdom-based fisheries technology and support fishermen empowerment programs.